Dietary modulation shapes gut microbiota and digestive physiology associated with specialized frugivory in Teratoscincus roborowskii - Yang, Yi; Feng, Huawei; Wang, Ziyi; Wu, Ruichen; Zheng, Yuhan; Wu, Xunheng (Frontiers in Microbiology, 2026)
Diet plays a key role in determining the composition and function of the gut microbiota. Teratoscincus roborowskii inhabits extreme desert environments and displays a unique frugivorous behavior. To investigate the relationship between its gut microbiota and metabolites associated with this specialized diet, the gut microbiota and key metabolite variations in T. roborowskii fed varying proportions of Capparis spinosa (capers) were analyzed using 16S rRNA sequencing and metabolomic profiling. Our results showed that trypsin activity was significantly higher in the mealworms group than in the capers groups. In contrast, the lipase activity was the highest in the capers-80% group, and the α-amylase activity was the highest in the capers-50% group. These patterns indicate that digestive enzyme activity reflects dietary composition. In addition, T. roborowskii fed either mealworm or caper-based diets shared the same dominant microbiota at the phylum level. However, the inclusion of capers significantly increased the abundance of Blautia in T. roborowskii, which are enriched in folate biosynthesis and purine metabolism pathways, supporting the idea that changes in diet can rapidly reshape the gut microbiota. Notably, diet, gut microbiota, digestive enzymes, and fecal metabolites are closely linked and interact with each other, indicating that T. roborowskii can adapt to dietary changes by modulating its gut microbiota and digestive physiology. Our study offers valuable insights into the gut microbiota of desert lizards and warrants further exploration of the relationship between desert lizards and desert plants.